Biomechanical analysis of a change-of-direction task in college soccer players - Condello, G.; Kernozek, T. W.; Tessitore, A.; Foster, C. (International Journal of Sports Physiology and Performance, 2016)
This study aimed to investigate biomechanical parameters during a change-of-direction task in college soccer players. Fourteen male and 12 female players performed a 10-m sprint with a 60° change of direction at 5 m. Vertical and mediolateral groundreaction force (GRF) and contact time were measured by having the subjects run in both directions while contacting a force plate with either their preferred (kicking) or nonpreferred leg. Using the midpoint between 2 pelvic markers, further parameters were evaluated: performance cutting angle and horizontal distance. Relationships between parameters, sex, and leg preference were analyzed. Significant correlations emerged between vertical and mediolateral GRF (r = .660-.909) and between contact time and performance cutting angle (r = -.598 to -.793). Sex differences were found for mediolateral GRF (P = .005), performance cutting angle (P = .043), and horizontal distance (P = .020). Leg differences were observed for vertical GRF (P = .029), performance cutting angle (P = .011), and horizontal distance (P = .012). This study showed that a sharper change of direction corresponded to a longer contact time, while no relationships were found with GRF. Moreover, measuring the angle revealed that the real path traveled was different from the theoretical one, highlighting the performance of sharper or more rounded execution. In conclusion, this study showed that specific biomechanical measurements can provide details about the execution of a change of direction, highlighting the ability of the nonpreferred leg to perform better directional changes.